Internal
problem
ID
[5659]
Book
:
Ordinary
differential
equations
and
their
solutions.
By
George
Moseley
Murphy.
1960
Section
:
Various
37
Problem
number
:
1104
Date
solved
:
Monday, January 27, 2025 at 01:01:52 PM
CAS
classification
:
[_rational]
✗ Solution by Maple
dsolve(x^2*(diff(y(x),x)^6+3*y(x)^4+3*y(x)^2+1) = a^2,y(x), singsol=all)
✗ Solution by Mathematica
Time used: 0.000 (sec). Leaf size: 0
DSolve[x^2 ( (D[y[x],x])^6 +3 (y[x])^4 +3 (y[x])^2 + 1)==a^2,y[x],x,IncludeSingularSolutions -> True]
Not solved